Development of Worksheet Based on Search Solve Create and Share (SSCS) on Learning Interest, Science Process Skills and Student Learning Outcomes in Biology Material of First Level (X Class) Senior High School - Josephine Olivia Gultom; Idramsa Idramsa; Fauziyah Harahap (Universitas Labuhanbatu, 2024)
This study develops and tests (LKPD) based on search, solve, create, and share (SSCS) in biology learning for class X MIA Semester I at SMA Negeri 5 Medan. To actively assess students' learning interests, science process skills, and learning outcomes at school because this process helps students search, find, and build their knowledge to solve problems. This research is development. Uses 4D development research (Define, Design, Develop, Disseminate). Interviews, material expert validation questionnaires, design validation questionnaires, language validation questionnaires, study field teacher responses to SSCS-based LKPD, student learning interest questionnaires, student science process skills questionnaires, and pretest-posttest assessment sheets were used. Material experts rate material validity as